The Implementation Of Teaching Writing At English Department Of Muhammadiyah UniversityOf Surakarta In 2015/2016 Academic Year - Riyanti, Atin Wahyu, Prof. Dr. Endang Fauziati, M.Hum, Siti Fatimah, S.Pd, M.Hum (2016)
This research aims to describe and to explain the implementation of TeachingWriting at English Department of Muhammadiyah University of Surakarta in 2015/2016 Academic Year. The objective of study is to describe the Implementation of TeachingWriting at English Department of Muhammadiyah University of Surakarta. In this research, there are eight component of teaching writing, namely: (1)Syllabus (2) Learning Objective (3) Classroom Procedure and Classroom Technique (4) Teacher Role (5) Learner Role (6) Teaching Media (7) Instructional Material (8) Assessment Model. The type of the research is descriptive qualitative reasearch. In this research, the data are derived from field note, interview, event, informan, and document. There are three method of collecting data, namely: observation, interview, and document. Technique for analyzing data are reduction of the data, display of the data, and conclusion / verification. The results of the research are: (1) The syllabus used is structural syllabus (2) There are two learning objectives, they are general learning objectiveand specific learning objectives (3) The classroom procedures used are explanation, giving example, giving exercise, correction, and in the classroom techniques used are presentation and practice (4) The teacher roles are facilitator, manager, instructor and evaluator (5) The leaner roles are learners monitor and evaluate their own progress, learners learn from the teacher (6) The media used are laptop, white board and lcd (7) The instructional material used is printed material (handbook) (8) The assessment models used are daily test, middle test, and final test.